Ellenőri korrupció, 1998 (Szociológiai Szemle, 2024)
In this paper I analyse a special group of organizations and occupation, i.e. the inspectorates and inspectors and the aim of the game is to measure the role of certain factors influencing the probability of corruption. The research was carried out by TÁRKI in 1995, 1997, and 1998. The three surveys covered the major organizations the main (or at least one of their) task of which was to monitor, regulate, and ispect the various transactions of the informal economy.The three proxies I developed to measure the level of corruption were as follows:- In past month how many times have you been offered bribe?- In past month how many times have you been offered gift?- In past month how many times have you been threatened?